Promoção do conhecimento organizacional: ações de gestão da informação e do conhecimento no setor contábil da UFPB - Lira, Suzana de Lucena (2012)
The growing concern about information and knowledge as factors contributing to the transformation of society, has stimulated research that might catch a glimpse of its management process, in order to preserve them in organizations. This study discusses the importance of information management and knowledge management (IKM) in an institution of higher education. Given the rapid growth process of the Federal University of Paraíba (UFPB), it is believed that the management of information and knowledge can contribute to consolidate the process of modernization of the institution, which requires increasingly prioritizing models that include knowledge generation and its permanence in the organization. It focuses on the stimulus, which can be implemented through assertive actions in creating and maintaining organizational knowledge, and as general purpose, analyze the actions of information management and knowledge of the technical staff of the Department of Accounting and Finance UFPB. In the methodological aspect, the research is characterized as a case study and field, appears as a study of qualitative and quantitative, exploratory and descriptive. Used as instruments of data collection a questionnaire individually, without identification, which allowed us to recognize the actions of GIC through the "diagnostic knowledge management," in view of Bukowitz and Williams, adopted as a parameter, and the technique of direct observation, performed by means of notes in field diary. For organizing and analyzing data, we used content analysis. The results show that the findings of the survey were positive for the actions of GIC, especially in the categories: get information and build and maintain the intellectual capital, although there was a need for improvements with regard to encouraging the sharing of knowledge in the sectors that make the Department of Accounting and Finance UFPB.